Jon Hall, Politeness and Politics in Cicero’s Letters, Oxford, Oxford University Press, 2009, xi + 275 pp. ISBN. 978-0-19-532906-3 (Minerva, 2019)
Review: Jon Hall, Politeness and Politics in Cicero’s Letters, Oxford, Oxford University Press, 2009, xi + 275 pp. ISBN. 978-0-19-532906-3